The Islamic worldview, knowledge and civilization: implementing the vision and mission of IIUM - Spahic, Omer (IslamiCity, 2018)
The International Islamic University Malaysia (IIUM) was established in 1983. Its vision is “to become a leading international centre of educational excellence which seeks to restore the dynamic and progressive role of the Muslim Ummah in all branches of knowledge and intellectual discourse”. Its mission is abridged in the notions and values of integration, Islamization, internationalization and comprehensive excellence.